2008
DOI: 10.1177/000348940811701207
|View full text |Cite
|
Sign up to set email alerts
|

Damage to Ciliated Epithelium in Chronic Rhinosinusitis: What is the Role of Bacterial Biofilms?

Abstract: The high percentage of biofilms in our specimens confirms the association between biofilms and CRS. Our data support the hypothesis that biofilm formation represents the latter phase of an inflammatory process that leads to complete epithelial destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
55
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 16 publications
5
55
1
2
Order By: Relevance
“…Thus, as stated by Galli et al, biofilm formation represents the later phase of the inflammatory process that leads to complete epithelial destruction. 28 The results of the present study clearly showed restoration of epithelium and cilia after treatment with SF-NS solutions. This can easily be considered as the consequence of biofilm removal by silver nanoparticles.…”
supporting
confidence: 70%
“…Thus, as stated by Galli et al, biofilm formation represents the later phase of the inflammatory process that leads to complete epithelial destruction. 28 The results of the present study clearly showed restoration of epithelium and cilia after treatment with SF-NS solutions. This can easily be considered as the consequence of biofilm removal by silver nanoparticles.…”
supporting
confidence: 70%
“…Furthermore, absence of bioWlms was not associated to the single employment of histopathological staining protocols or OCT scans. CRSwNP is a disease of multifactorial agents involving disturbed local immune response and chronic inXammation; however, bioWlms might contribute to the damage of respiratory epithelium and subsequent hyperplasia of the [2,6,12]. Although speciWc treatments are not available to target bioWlms, it is very important to be detected, since it is strongly associated with treatment failure and persisting symptoms [1,2,30].…”
Section: Discussionmentioning
confidence: 99%
“…BioWlms are characterized by a self-produced threedimensional extracellular matrix that consists of water, polysaccharides, proteins, and nucleic acids [7,9]. This complex structure provides extremely high resistance against antimicrobial agents and host immune reactions [6,7,12]. This resistance mechanism is based on the physical barrier formed by the polysaccharide matrix that blocks the diVusion of antibiotics, antimycotics, superoxides, immunglobulins, and opsonins [6,7,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Middle ear damage from early events may result in increasingly complex, often polymicrobial OM episodes [1,3], with a diminishing relative role of S. pneumoniae (especially PCV13 serotypes) [4][5][6] and an increasing NTHi role, often in association with mixed infections and biofilm formation [7][8][9][10][11]. NTHi is also a major pathogen in other recurrent, nonresponsive and chronic respiratory infections [12][13][14][15].…”
mentioning
confidence: 99%